Hazarat LUT (AS) - Karam , Ambia (Lahore , Karachi children's publication)
According to Islamic tradition, Lut was born to Haran and spent his younger years in Ur, later migrating to Canaan with his uncle Abraham. He was sent to the cities of Sodom and Gomorrah as a prophet, and was commanded to preach to their inhabitants on monotheism.